2009
DOI: 10.1007/s00125-009-1413-9
|View full text |Cite
|
Sign up to set email alerts
|

Combined effects of single-nucleotide polymorphisms in GCK, GCKR, G6PC2 and MTNR1B on fasting plasma glucose and type 2 diabetes risk

Abstract: Aims/hypothesis Variation in fasting plasma glucose (FPG) within the normal range is a known risk factor for the development of type 2 diabetes. Several reports have shown that genetic variation in the genes for glucokinase (GCK), glucokinase regulatory protein (GCKR), islet-specific glucose 6 phosphatase catalytic subunit-related protein (G6PC2) and melatonin receptor type 1B (MTNR1B) is associated with FPG. In this study we examined whether these loci also contribute to type 2 diabetes susceptibility. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
47
1
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(58 citation statements)
references
References 21 publications
9
47
1
1
Order By: Relevance
“…The associations of GCK and GCKR polymorphisms with glucose metabolism disorders have been also well described [27,28], and our study results were in line with these previous findings, underscoring the importance of these associations. We also observed a possible risk reduction of dyslipidemia in those with GCKR rs780094 G/G genotype or GCKR rs1260326 C/C genaction between GCKR rs780094 A/A genotype and low carbohydrate intake (OR for interaction = 1.73; 95% CI 1.06-2.84, P = 0.030) on the risk of dyslipidemia (Table 6).…”
Section: Gene-environment Interaction Between Lifestyle Factors and Psupporting
confidence: 92%
“…The associations of GCK and GCKR polymorphisms with glucose metabolism disorders have been also well described [27,28], and our study results were in line with these previous findings, underscoring the importance of these associations. We also observed a possible risk reduction of dyslipidemia in those with GCKR rs780094 G/G genotype or GCKR rs1260326 C/C genaction between GCKR rs780094 A/A genotype and low carbohydrate intake (OR for interaction = 1.73; 95% CI 1.06-2.84, P = 0.030) on the risk of dyslipidemia (Table 6).…”
Section: Gene-environment Interaction Between Lifestyle Factors and Psupporting
confidence: 92%
“…It has been debated whether the genetic determinants regulating FPG levels in physiological states differ from those increasing type 2 diabetes risk. Some studies report that carriers of glucose-increasing alleles at three loci (MTNR1B, GCK and GCKR) show a higher risk of type 2 diabetes [8,17,18], although there is no significant association between G6PC2-ABCB11 variants and type 2 diabetes in populations of European descent [14,17,35]. In this context, our data not only supported the concordant association of G6PC2-ABCB11 variants for FPG and type 2 diabetes in two Asian populations, but also indicated that genetic determinants regulating FPG levels could, at least in part, differ from those increasing type 2 diabetes risk (ESM Fig.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been demonstrated that human islets express GKRP at very low levels ). This issue should be revisited because of the recent publication of several genome-wide association studies that associate GK, GCKR, G6PC2, MTNR1B with type 2 diabetes risk linked to -cell function (Reiling, 2009& Bonetti, 2011. Whether, -cell GK function is affected directly by a hypothetic pancreatic GKRP, or indirectly by liver GKRP impaired activity, still needs clarification.…”
Section: Gkrp Modulates the Impact Of Gk Activity On Glucose And Lipimentioning
confidence: 99%
“…Finally glucose-6-phosphatase deficiency causes severe hyperlipidemia and hepatic steatosis (Bandsma, 2002(Bandsma, , 2008, therefore giving rise that this enzyme may also participate or influence the GK/GKRP system in the regulation of hepatic glucose fate. To support this hypothesis, Reiling and colleagues described combined effects of single-nucleotide polymorphisms in GK, GKRP and glucose-6-phosphatase on fasting plasma glucose and type 2 diabetes (Reiling, 2009). Therefore, it is a field that needs further exploration.…”
Section: Gkrp Modulates the Impact Of Gk Activity On Glucose And Lipimentioning
confidence: 99%